Further evidence on the relationship between abdominal aortic aneurysm and periodontitis: A cross‐sectional study. Issue 11 (8th July 2020) - Salhi, Leila; Sakalihasan, Natzi; Okroglic, Ambre Gau; Labropoulos, Nicos; Seidel, Laurence; Albert, Adelin; Teughels, Wim; Defraigne, Jean‐Olivier; Lambert, France
Abstract: Background: Periodontitis is a chronic inflammatory disease characterized by Gram‐negative bacteria responsible for the degradation of tissues surrounding tooth. Moreover, periopathogens can invade the bloodstream, disseminate and promote cardiovascular disease, such as the link between Porphyromonas gingivalis and atherosclerosis. The aim of this study was to explore the relationship between the severity of periodontitis and of abdominal aortic aneurysm (AAA). Methods: This cross‐sectional study compared patients with stable AAA (n = 30) and patients with unstable AAA (n = 31) based on aortic diameter, growth rate, and eligibility for surgical intervention. Periodontal clinical parameters were recorded as well as the Periodontal Inflamed Surface Area and the Periodontal Index for Risk of Infectiousness (PIRI). Microbiological analyses were performed on saliva and supragingival and subgingival plaque. Quantification of Tannerella forsythia (Tf), Porphyromonas gingivalis (Pg), Aggregatibacter actinomycetemcomitans (Aa), Fusobacterium nucleatum (Fn), and Prevotella intermedia (Pi) was done by quantitative polymerase chain reaction. Results: The two AAA groups were homogeneous for age, sex, and most risk factors except hypertension and chronic obstructive pulmonary disease. Periodontal parameters were comparable but the proportion of patients with high PIRI scores was greater in those with unstable AAA (51.6% versus 23.3%). The probing depth (PD) and the proportion of PD >6 mm were positively correlated with AAA size and thrombus volume. Several associations were found between periopathogens such as Pg and AAA diameters and volumes, but no difference could be evidenced between stable and unstable AAA groups. Conclusions: Periodontitis was highly prevalent in both stable and unstable AAA patients. Severe and progressive periodontitis (stage IV and grade C) tended to be more frequent in the group of patients with unstable AAA. Moreover, Pg was observed in all the samples (saliva, supragingival, and subgingival plaque) and was correlated with AAA diameters and volumes. The study evidenced potential relationships between periodontitis severity and size of AAA.